Predation follows competition in depth selection behaviour of Cladocera in a deep lake (E Poland) - Adamczuk, Małgorzata (Biological Letters, 2010)
Observations of the vertical distribution of Cladocera in the pelagic zone of the deep Lake Piaseczno (38.8 m) focused on 6 species: Diaphanosoma brachyurum, Daphnia longispina, D. cucullata, Bosmina coregoni, B. longirostris, and Chydorus sphaericus. The animals displayed clear depth preferences, and their migration patterns were limited to small depth amplitudes. The results show that vertical habitat segregation of cladocerans in the lake consists mostly in the mechanism of competition for accessible food resources, rather than in the mechanism of predation avoidance.